Diskurse - digital Theorien, Methoden, Anwendungen - Gredel, Eva (Diskursmuster / Discourse Patterns, 2022)
The aim of this publication is to expand the program and methodological inventory of discourse linguistics in two ways: firstly, by systematizing the specific descriptive categories and analytical tools available for discourses in digital media (e.g., hashtags). Secondly, it seeks to evaluate and develop digital methods and the methods and tools of corpus linguistics to meet the requirements of discourse linguistics.